Hubungan Komunikasi Terapeutik Dengan Mutu Pelayanan Kesehatan Keperawatan Di Upt Puskesmas Simpang Tiga Pekanbaru - haniah, Naila; Emulyani; Herniyanti, Rina; Devita, Yeni (Bunda Edu-Midwifery Journal (BEMJ), 2026)
The quality of nursing services is an important indicator in assessing the quality of healthservices at community health centers as primary health care facilities. One of the factorsthat influences service quality is the implementation of therapeutic communication bynurses. Effective therapeutic communication can build trust between nurses and patients,increase patient satisfaction, and support the success of nursing care. Based onpreliminary observations at UPT Simpang Tiga Public Health Center, Pekanbaru, therewere still patient complaints related to the lack of explanation, empathy, andresponsiveness of nurses in providing services.This study aims to determine the relationship between therapeutic communication and the quality of nursing health servicesat UPT Simpang Tiga Public Health Center, Pekanbaru. The study was conducted fromJanuary 7 to January 13, 2026, using a quantitative method with a correlational design.The sample consisted of 104 respondents selected using an accidental sampling technique.Data were collected using therapeutic communication and nursing service qualityquestionnaires. Data analysis was conducted using bivariate analysis with the Chi-Squaretest.The results showed that most respondents assessed nurses’ therapeutic communication as good (52.9%) and nursing service quality as satisfactory (56.7%). Statistical test results showed a p-value of 0.001 (<0.05), indicating a significant relationship between therapeutic communication and the quality of nursing services. The better the therapeutic communication applied by nurses, the better the quality of nursing services perceived by patients.Therefore, it is recommended that the community health center improve the quality of services through ongoing therapeutic communication training and evaluation of nurse performance.